Lactiplantibacillus plantarum N-1 improves autism-like behavior and gut microbiota in mouse - Qiu, Zhongqing; Luo, Dongmei; Yin, Heng; Chen, Yajun; Zhou, Zhiwei; Zhang, Jing; Zhang, Linzhu; Xia, Jinrong; Xie, Jiang; Sun, Qun; Xu, Wenming (Frontiers in Microbiology, 2023)
The gut-brain axis has been widely recognized in autism spectrum disorder (ASD), and probiotics are considered to potentially benefit the rescuing of autism-like behaviors. As a probiotic strain, Lactiplantibacillus plantarum N-1(LPN-1) was utilized to investigate its effects on gut microbiota and autism-like behaviors in ASD mice constructed by maternal immune activation (MIA). Adult offspring of MIA mice were given LPN-1 at the dosage of 2 × 109 CFU/g for four weeks before subject to the behavior and gut microbiota evaluation. The behavioral tests showed that LPN-1 intervention was able to rescue autism-like behaviors in mice, including anxiety and depression. In which the LPN-1 treatment group increased the time spent interacting with strangers in the three-chamber test, their activity time and distance in the central area increased in the open field test, and their immobility time decreased when hanging their tails. Moreover, the supplementation of LPN-1 reversed the intestinal flora structure of ASD mice by enhancing the relative abundance of the pivotal microorganisms of Allobaculum and Oscillospira, while reducing those harmful ones like Sutterella at the genus level. These results suggested that LPN-1 supplementation may improve autism-like behaviors, possibly via regulating the gut microbiota.